Efforts to overcome student absenteeism - Bayowe, Meilan (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
This research was conducted based on the fact that there were many students who came late to school and the increasing number of student attendance. Therefore, the counseling teacher tries to reduce the tardiness and attendance of these students by conducting individual counseling services. To further maximize the expected results using an individual counseling approach electrical techniques. The subjects of this study were 5 students in class VIII. The benefits of the expected that students who are absent and late coming to school every day can increase the frequency of their absence to be present every day. besides that it can also be used as a reference in providing individual counseling services, and peers as observers. The results showed that the implementation of service actions was carried out in two cycles, where each cycle consisted of four stages, namely; (a) planning, (b) implementation, (c) observation, and (d) reflection. After analyzing the results after the implementation of individual counseling with electrical techniques, there was a reduction in the frequency of absenteeism of class VIII students. From the results of the research, it is suggested that the counseling teacher should record and monitor students who are late coming to school, because there are still class teachers and counseling teachers who are indifferent to the students' indiscipline.